2017
DOI: 10.1002/acr.23139
|View full text |Cite
|
Sign up to set email alerts
|

Early High‐Intensity Versus Low‐Intensity Rehabilitation After Total Knee Arthroplasty: A Randomized Controlled Trial

Abstract: Objective The purpose of this study was to examine the safety and efficacy of a high-intensity progressive rehabilitation protocol (HI) beginning 4 days after total knee arthroplasty (TKA) compared to a low-intensity (LI) rehabilitation protocol. Methods One hundred sixty-two participants (aged 63±7 years; 89 females) were randomized to either the HI group or LI group after TKA. Key components of the HI intervention were the utilization of progressive resistance exercises and a rapid progression to weight-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
116
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(140 citation statements)
references
References 29 publications
5
116
0
4
Order By: Relevance
“…3133 Recruitment across all studies was restricted to patients who underwent an elective unilateral TKA for the treatment of OA and were between 50–85 years of age. Exclusion criteria in all studies included uncontrolled hypertension, uncontrolled diabetes, significant neurologic impairments, contralateral knee osteoarthritis (as defined by a pain level of greater than 4/10 with activity), the presence of other unstable lower-extremity orthopedic conditions, and a body mass index (BMI) greater than >40 kg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…3133 Recruitment across all studies was restricted to patients who underwent an elective unilateral TKA for the treatment of OA and were between 50–85 years of age. Exclusion criteria in all studies included uncontrolled hypertension, uncontrolled diabetes, significant neurologic impairments, contralateral knee osteoarthritis (as defined by a pain level of greater than 4/10 with activity), the presence of other unstable lower-extremity orthopedic conditions, and a body mass index (BMI) greater than >40 kg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Between 2003 and 2012, the incidence of TKA increased from 145.4 to 223.0 per 100,000 people in Australia [4]. Over 700,000 TKAs are performed each year in America to alleviate the pain and disabilities associated with knee osteoarthritis [5].…”
Section: Introductionmentioning
confidence: 99%
“…In their recent article published in Arthritis Care & Research, Bade et al examined the safety and efficacy of high-intensity versus low-intensity rehabilitation protocols (1). We read the article with interest and noted that the study showed essentially no differences at either 3 or 12 months between the training groups in functional performance, patient-reported outcomes, and muscle strength.…”
mentioning
confidence: 96%
“…We have previously published a systematic review on progressive resistance training before and after total knee arthroplasty (2). We found that the methodologic quality of existing evidence did not permit us to reach a conclusion on the effectiveness of progressive resistance training before and/or after total knee arthroplasty, and we are therefore encouraged that studies on this topic are now emerging (1,3). There seems to be a growing body of evidence suggesting that high-intensity training initiated in the early postoperative phase after total knee arthroplasty, does not result in better outcomes (1,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation